1995
DOI: 10.1021/jm00019a013
|View full text |Cite
|
Sign up to set email alerts
|

Furanfurin and Thiophenfurin: Two Novel Tiazofurin Analogs. Synthesis, Structure, Antitumor Activity, and Interactions with Inosine Monophosphate Dehydrogenase

Abstract: The syntheses of furan and thiophene analogues of tiazofurin (furanfurin and thiophenfurin, respectively) are described. Direct stannic chloride-catalyzed C-glycosylation of ethyl 3-furan-carboxylate (6) or ethyl 3-thiophencarboxylate (18) with 1,2,3,5-tetra-O-acetyl-D-ribofuranose gave 2- and 5-glycosylated regioisomers, as a mixture of alpha- and beta-anomers, and the beta-2,5-diglycosylated derivatives. Deprotection of ethyl 5-(2,3,5-tri-O-acetyl-beta-D-ribofuranosyl)furan-3-carboxylate (9 beta) and ethyl 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 21 publications
5
82
0
1
Order By: Relevance
“…8 When applied to carbonitrile thiophenes, this method failed to yield any C-glycosylation product. Attempts to introduce any other types of thiophenes, including the ethyl thiophene carboxylate employed by Franchetti and thiophene itself, either led to no product formation or polymerised unidentifiable material.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…8 When applied to carbonitrile thiophenes, this method failed to yield any C-glycosylation product. Attempts to introduce any other types of thiophenes, including the ethyl thiophene carboxylate employed by Franchetti and thiophene itself, either led to no product formation or polymerised unidentifiable material.…”
Section: Chemistrymentioning
confidence: 99%
“…8 In his study, he observed that the S-atom remained cis to the furanose-oxygen and ab initio calculations suggested that this conformation was stabilised by an electrostatic interaction between a positively charged thiophene sulfur and a negatively charged furanose oxygen. Therefore, based on these observations, we could assume similar restricted rotation around the C-glycosidic bond of 7ab and 7bb.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them possess antiviral or antineoplastic activities. [1] Quite recently, C-nucleosides bearing simple hydrophobic aryl and hetaryl groups as nucleobase surrogates attracted great attention due to their use in the extension of the genetic alphabet. [2] If incorporated to oligonucleotides, they selectively pair with the same of other hydrophobic nucleobase to form stable duplexes due to increased stacking and favourable desolvation energy as compared to canonical nucleobases.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In more recent studies, a series of isomeric dideoxynucleosides was synthesized in our laboratory. synthesized and studied the unusual isomeric C-dideoxynucleoside, 4(S)-(4-carbamoyl-thiazol-2-yl)-tetrahydro-2(S)-furan-methanol 4 and this paper describes the results of our synthesis and antiviral studies.…”
Section: Introductionmentioning
confidence: 99%